(untitled) (Bangladesh Journal of Genetics and Biotechnology, 2008)
No abstract available. Key words: Honey; antibacterial activity; pathogen; gram positive; gram negative Bangladesh j. genet. biotechnol. 6 (1&2): 55-58, 2005 (June & December)